ANALISIS PERAN STAKEHOLDERS DALAM PENGEMBANGAN PARIWISATA DI DESA WISATA JATIREJO, KECAMATAN GUNUNGPATI, KOTA SEMARANG - Fahad Mursyid Jannata; Aufarul Marom; Herbasuki Nurcahyanto (Journal of Public Policy and Management Review, 2023)
Developmnent is not only in the infrastructure sector, but also in various fields including tourism. One of the tourism destinations in Semarang City is the Jatirejo Tourism Village. In the beginning, the management of this tourist village was quite good, but as the years goes by, ii is safe to say that the management weren't as optimal as it should be. This is caused by weak coordination between tourism stakeholders for synchronization and harmonization. This research aims to identify stakeholders in policy implementation, identify stakeholders in tourism deelopment, analyze the role af stakeholders, and analyze supporting and inhibiting factors in tourism development in Jatirejo Tourism Village. This research conducted by qualitative descriptive method by collecting data through observation, interviews and documentation. The result of the research shows that the stakeholders in implementing the Pentahelix-shaped policy consist of academics, by Kedaireka Team; from the private sector, represented by BNI: from the community, involving Pokdarwis Jatirejo, Karang Taruna Jatirejo, PKK Jatirejo, KTT "Sido Makmur", KWT Jatirejo Village, and UMKM Ala Siranda: from the government, inchuding Mayor of Semarang, Disbudpar, Jatirejo Subdistrict, Bapeda, Dispertan, DinkopUM, Dishanpan, Dinkes, and Disperkim; also from the mass media, represented by Radar Semarang. The identification of stakeholders based on influence and interests is divided into primary, secondary and tertiary stakeholders, whereas for quarterly there were no such stakeholders. In addition, the role of stakeholders consists of policy creator, coordinator., facilitator, implementor and accelerator. Also in tourism development, there are Supporting and inhibiting factors originating from indicators of values, communication, trust and policy. Stakeholders are expected to improve relations of harmony and synchronism, stakeholders can carry out their respective duties and functions optimally. It is expected that community awareness and concern for the tourist village increasing gradualy also restructurisation and veorganization of Jatirejo Pokdarwis' Management.